External comparator studies and the joint application of the estimand and target trial emulation frameworks - Rippin, Gerd; Sanz, Héctor (Frontiers in Drug Safety and Regulation, 2024)
The Estimand Framework (EF) and the Target Trial Emulation Framework (TTEF) are two important frameworks that can inform the design and analysis of External Comparator (EC) studies. The EF helps clarifying the quantity which is aimed to be estimated (the estimand), especially regarding the handling of post-baseline intercurrent events which interfere with the existence or interpretation of endpoints. Similarly, the TTEF is instrumental for specifying key design components of a hypothetical randomized trial and identifying which of those an EC study can and cannot emulate. We offer considerations about the joint application of both frameworks by combining the 5 EF attributes treatment, population, endpoint, intercurrent events, and population-level summary with the 7 TTEF components eligibility criteria, treatment strategies, assignment procedures, follow-up period, outcomes, causal contrasts, and data analysis plan. Any overlap is identified, as well as omissions and unique contributions from both frameworks. Furthermore, specific considerations when applying these joint elements to EC studies are highlighted.